Bahasa Inggris - Iqbal, Mohammad (Ekspektra : Jurnal Bisnis dan Manajemen, 2023)
This study investigated the effect of ESG Score on firm performance (operational, financial, and market) in environmentally sensitive industries. This study analyzed the effect of ESG score to firm performance before and during the Covid-19 pandemic crisis in emerging market countries to see from different perspectives to complement the gaps in existing research. To test the hypotheses, researcher used regression with panel data using the Thomson Reuters Refinitiv Eikon™ database to analyzed data from 704 environmentally sensitive listed companies selected from 16 emerging market countries between 2016 and 2021. The findings obtained from the empirical results showed that there was no significant relationship between ESG Score and operational performance (ROA), financial performance (ROE) and market performance (TQ) of companies before the Covid-19 pandemic crisis. Another finding was that there was no significant relationship between ESG Score and ROA, ROE and TQ during the pandemic crisis. This study highlights whether the Covid-19 pandemic contributes to the relationship between ESG Score and firm performance, especially for environmentally sensitive industries in emerging market countries.